Therapeutic potential of nanotechnology-based approaches in osteoarthritis - Xiao, Likang; Cui, Jiarui; Sun, Zhuang; Liu, Yunke; Zheng, Jia; Dong, Yonghui (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a multifactorial disease that affects the entire joint, often resulting in severe pain, disability, psychological distress, and a lower quality of life. Patient self-management is emphasized in OA clinical recommendations. Currently, the clinical treatment of OA mainly focuses on pain relief and the improvement of joint function, with few options for regenerating degenerative cartilage or slowing the progression of OA. Therefore, we first reviewed the current treatment of OA, and then summarized the research advances of nanotechnology in OA treatment, including nano drug delivery systems for small molecule drugs, nucleic acids and proteins, nano-scaffolds for cartilage regeneration, and nanoparticle lubricants. Finally, we discussed the opportunities and potential challenges of nanotechnology in OA treatment.